'HOW I BECAME A COMPOSER': AN INTERVIEW WITH VINKO GLOBOKAR. (3rd January 2014) - Goldman, Jonathan
Abstract This article is an interview with the Franco-Slovenian composer, conductor and trombonist Vinko Globokar, translated, edited and introduced by the author. It offers an overview of Globokar's musical development and a consideration of his artistic position, which straddles the worlds of composition and improvisation. Globokar's music combines complex organisation with an interest in non-hierarchical and improvisatory elements. He has always refused to pit the avant-garde claims of contemporary music against those of free jazz, his music embracing aspects of both, as well as of traditional Balkan musics. His genre-defying approach remains better known in continental Europe than in the UK or North America, and the present text is a contribution to the limited bibliography on Globokar in English.